Management of penetrating extraperitoneal rectal injuries: An Eastern Association for the Surgery of Trauma practice management guideline. Issue 3 (March 2016) - Bosarge, Patrick L.; Como, John J.; Fox, Nicole; Falck-Ytter, Yngve; Haut, Elliott R.; Dorion, Heath A.; Patel, Nimitt J.; Rushing, Amy; Raff, Lauren A.; McDonald, Amy A.; Robinson, Bryce R.H.; McGwin, Gerald; et al.
Abstract : BACKGROUND: The management of penetrating rectal trauma invokes a complex decision tree that advocates the principles of proximal diversion (diversion) of the fecal stream, irrigation of stool from the distal rectum, and presacral drainage based on data from World War II and the Vietnam War. This guideline seeks to define the initial operative management principles for nondestructive extraperitoneal rectal injuries. METHODS: A systematic review of the MEDLINE database using PubMed was performed. The search retrieved English language articles regarding penetrating rectal trauma from January 1900 to July 2014. Letters to the editor, case reports, book chapters, and review articles were excluded. Topics of investigation included the management principles of diversion, irrigation of stool from the distal rectum, and presacral drainage using the GRADE methodology. RESULTS: A total of 306 articles were screened leading to a full-text review of 56 articles. Eighteen articles were used to formulate the recommendations of this guideline. CONCLUSION: This guideline consists of three conditional evidence-based recommendations. First, we conditionally recommend proximal diversion for management of these injuries. Second, we conditionally recommend the avoidance of routine presacral drains and distal rectal washout in the management of these injuries.